Dropwise Condensation Heat Transfer on Plasma-Ion-Implanted Small Horizontal Tube Bundles - Kananeh, Ali Bani; Rausch, Michael Heinrich; Leipertz, Alfred; Fröba, Andreas Paul (Heat Transfer Engineering, 2010)
Stable dropwise condensation of saturated steam was achieved on stainless-steel tube bundles implanted with nitrogen ions by plasma ion implantation. For the investigation of the condensation heat transfer enhancement by plasma ion implantation, a condenser was constructed in order to measure the heat flow and the overall heat transfer coefficient for the condensation of steam on the outside surface of tube bundles. For a horizontal tube bundle of nine tubes implanted with a nitrogen ion dose of 10(16) cm(-2), the enhancement ratio, which represents the ratio of the overall heat transfer coefficient of the implanted tube bundle to that of the unimplanted one, was found to be 1.12 for a cooling-water Reynolds number of about 21,000. The heat flow and the overall heat transfer coefficient were increased by increasing the steam pressure. The maximum overall heat transfer coefficient of 2.22 kW.m(-2).K(-1) was measured at a steam pressure of 2 bar and a cooling-water Reynolds number of about 2,000. At these conditions, more dropwise condensation was formed on the upper tube rows, while the lowest row received more condensate, which converted the condensation form to filmwise condensation.